The Correlation Between Students’ Speaking Skills And Self-Directed Learning In Virtual English Community - Rizka Tiara Azizah SBH; Arik Susanti (Universitas Negeri Surabaya, 2021)
This study was conducted to investigate correlation between students' speaking skills and self-directed learning in a virtual English community. This quantitative research involved 20 students who joined the speaking community at a public university in Surabaya. It used speaking rubric and a questionnaire as instrument data and was then analyzed by using SPSS 26.0 for Windows. The result of this study was the students included moderate self-directed learning users. The highest mean score was self-management (M=3.79) and followed by self-motivation (M=3.64) and self-monitoring (M=3.34). In terms of speaking skills, the students were good speakers in every speaking aspect. Sequentially, the best speaking aspect mastered was vocabulary and followed by grammar & accuracy, pronunciation, and fluency & coherence. Through correlation analysis, the use of self-directed learning was highly correlated with the students' speaking skills (r=0.669). Thus, it could be said that applying self-directed learning is a helpful way for the students' speaking skills. Keywords: Speaking skills, self-directed learning, English community